PENGEMBANGAN DAN PENERAPAN VIDEO ANIMASI SEBAGAI MEDIA PEMBELAJARAN BAHASA UNTUK MENINGKATKAN MINAT BELAJAR PADA SISWA SMP NEGERI 16 KOTA JAMBI - Nurul Fitri; Ridho Praja Dinata; Willy Satria (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2024)
This research aims to develop and implement animated learning videos as supporting media in English language learning to enhance the interest in learning among eighth-grade students at SMP Negeri 16 in Jambi City. In addition, this research also aims to test the quality of the developed animated video products. This research uses a research and development method with the ADDIE model through the stages of analysis, design, development, and evaluation. Data collection was carried out using observation, interviews, and questionnaires. The data was analyzed using qualitative and quantitative descriptive analysis. Based on the validation results from two media experts, which scored 90% and 85%, this animated video is categorized as suitable for use as supporting teaching material in the learning process. Additionally, the animated video has also been validated by one content expert with a score of 90%, which also falls into the category of being appropriate for use as a learning medium. The results of the trial conducted on 35 eighth-grade students showed a percentage score of 83%, proving that the animated video designed as a learning medium is a very engaging video and can enhance students' interest in learning English.